Occupational Noise Exposure and Blood Pressure among Turbine Boiler Cleaning Workers at PLN Paiton - Nilla Roikhatul; Feronia Chiquita Hanum2; Noeroel Widajati (Tadulako University, 2026)
Occupational noise exposure in industrial environments serves as a physical stressor contributing to non-auditory health disorders, including elevated blood pressure. This study aims to analyze the association between noise intensity and the use of Hearing Protection Devices (HPD) with blood pressure among cleaning workers in the turbine and boiler areas of PT PLN Nusantara Power UP Paiton. The research employed an analytical observational method with a cross-sectional design. The sample consisted of 52 cleaning workers selected through simple random sampling. Data were collected by measuring noise intensity using a Sound Level Meter, assessing blood pressure before and after work shifts using a digital sphygmomanometer, and administering questionnaires regarding HPD usage. The results indicated that most noise intensity measurements in the work area exceeded the Threshold Limit Value (85 d.). Bivariate analysis using the Chi-square test showed a statistically significant association between noise intensity and systolic blood pressure (p = 0.008) and diastolic blood pressure (p = 0.016). In addition, HPD usage was also significantly associated with blood pressure (p = 0.015). This study concludes that high noise exposure and inconsistent HPD use are associated with increased blood pressure among workers. It is recommended that the company strengthen HPD compliance supervision and implement regular cardiovascular health monitoring.